Robotics and Well-Being - Aldinhas Ferreira, Maria Isabel; Silva Sequeira, João; Singh Virk, Gurvinder; Tokhi, Mohammad Osman; E. Kadar, Endre (Intelligent Systems, Control and Automation: Science and Engineering,, 2019)
This book highlights some of the most pressing safety, ethical, legal and societal issues related to the diverse contexts in which robotic technologies apply. Focusing on the essential concept of well-being, it addresses topics that are fundamental not only for research, but also for industry and end-users, discussing the challenges in a wide variety of applications, including domestic robots, autonomous manufacturing, personal care robots and drones.